The demise of Joshua according to Josephus - Begg, Christopher (HTS teologiese studies, 2007)
This article focuses on Josephus’ account of the end of Joshua in his Ant. 5.115-119. It offers a detailed comparison between that account and its biblical source (Jos 23-24) on the one hand, and two other postbiblical narrations of Joshua’s demise, that is those of Pseudo-Philo in Liber Antiquitatum Biblicarum 23-24 and the “Samaritan Chronicle No. II,” on the other. As compared with Joshua 23-24, Josephus’ version appears highly abbreviated, leaving aside, for example, the whole of Joshua 23 as well as 24:16-28, 31-32, even while also introducing various new elements. Josephus shares his non-reproduction of Joshua 23 and 24:31-32 with Pseudo-Philo and the Chronicle, for example, but deviates from these other witnesses in his downplaying of the role/activities of the dying Joshua.